2016
DOI: 10.22159/ijpps.2016v8i9.12846
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic Efficacy of Ethanolic Extract of Vitis Vinifera Leaves in Rats

Abstract: Objective: The ethanolic extract of Vitis vinifera leaves (VVE) (500 mg/kg body weight), ranitidine (50 mg/kg body weight) and both of them were tested for their gastroprotective and curative effects against the incidence of peptic ulcer. Methods:The antiulcer effects of VVE were investigated using a combination of indomethacin and cold-stress for 2h. To ascertain the mechanism of action of VVE, its protective and curative effects were studied on gastric volume, gastric juice acidity, ulcer index and malondial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Natural products were considered as a rich source of compounds for drug discovery [25]. Therefore, by scavenging free radicals, antioxidants from plant sources may play an important role in gastric ulcer therapy [26]. In accordance with this report, methanolic extract showed the highest scavenging capacity for 2,2-diphenyl-1-picrylhydrazyl radical, superoxide radical scavenging activity recorded in our study [14].…”
Section: Resultssupporting
confidence: 88%
“…Natural products were considered as a rich source of compounds for drug discovery [25]. Therefore, by scavenging free radicals, antioxidants from plant sources may play an important role in gastric ulcer therapy [26]. In accordance with this report, methanolic extract showed the highest scavenging capacity for 2,2-diphenyl-1-picrylhydrazyl radical, superoxide radical scavenging activity recorded in our study [14].…”
Section: Resultssupporting
confidence: 88%
“…The results suggested that a high dose of CB (3000 mg/kg) could be better in activating antioxidant factors than omeprazole was. As the terminal product of lipid peroxidation, MDA is introduced to indicate its level [ 42 , 43 ]. The level of MDA increased in indomethacin-induced gastric mucosal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The mucosal damage areas were expressed as a percentage of the total surface area of the glandular stomach estimated in square millimeters. The mean ulceration score for every animal was expressed as an ulceration index, and also the percentage inhibition against ulceration was determined using the expression as follows [7].…”
Section: Evaluation Of Ulcerationmentioning
confidence: 99%